Kesetaraan Gender dalam Manajemen Sumber Daya Insani: Tantangan dan Peluang - Rika Nur Amelia; Ananta Delyana Mafikah; Sifwatir Rif’ah (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2024)
Gender equality is a global issue that continues to be the main focus in human resource management (SDI). This article aims to analyze the opportunities and challenges of implementing gender equality in HR management using a qualitative-descriptive approach. Data was obtained through an in-depth literature review of previous research, organizational policies, and reports on modern management practices. The research results show that implementing gender equality has the potential to increase productivity, innovation and diversity in the workplace. However, there are significant challenges, such as gender stereotypes, pay inequality and limited access for women to strategic leadership positions. This article recommends strategies, including gender awareness training, work flexibility policies, and transparency in recruitment and promotion, as steps to address these challenges. This research is expected to provide practical insights for organizations in integrating gender equality values ​​as part of a sustainable HR management strategy.